Meninjau Pemberdayaan Masyarakat Desa Pandau Jaya Melalui Kebijakan Program Produk Unggulan Tahun 2019 - Ramlan Darmansyah (Departemen Ilmu Pemerintahan Fisip Unhas, 2020)
This study discusses the problem of empowering superior products in Pandau Jaya Village through a field study by the author. he discussion in this research examines the empowerment of the Pandau Jaya Village community through the Superior Product Program Policy in 2019 which is based on 4 priority programs of the Ministry of Village. Then the source of capital for this superior product empowerment program is through the Pandau Jaya Village Income and Expenditure Budget. The superior product in Pandau Jaya Village is the superior product of honey papaya which is an agricultural commodity. As for the formulation of the problem in this research, how is the empowerment of the people of Pandau Jaya Village through the superior product program policy in 2019? And what is the process of forming a community empowerment policy in Pandau Jaya Village through superior products?. The method in this research is descriptive qualitative research which emphasizes the words with interview and documentation data collection techniques. The result of this research is that the problem that occurs in the empowerment program for superior honey papaya products in Pandau Jaya Village is the involvement of community participation in the implementation of empowerment programs, innovation in managing superior products and community empowerment in terms of commodity independence of farmer groups who are not involved in the implementation, empowerment program.